2021
DOI: 10.1002/pld3.311
|View full text |Cite
|
Sign up to set email alerts
|

Gender discrimination of Populus tomentosa barks by HPLC fingerprint combined with multivariate statistics

Abstract: A high‐performance liquid chromatography (HPLC) fingerprint method with multivariate statistical analyses was applied to discriminate the male and female barks of Populus tomentosa for the first time. The samples of 11 male and 13 female barks of mature P. tomentosa were collected in Beijing. The chemical fingerprint of methanol extract was established by HPLC method with diode array detector (DAD). The principal component analysis (PCA), hierarchical clustering analysis (HCA), and supervised orthogonal partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…According to the standard and literature, combined with the polarity, 14 compounds were identified in Table 2 and Table S4 (Figures S3 – S18 ) [ 21 , 34 40 ]. The retention times at 8.91, 13.76, 17.37, and 18.14 min corresponded to the peaks 4, 9, 14, and 15 in the HPLC fingerprint by comparing the peak area, polarity, and spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the standard and literature, combined with the polarity, 14 compounds were identified in Table 2 and Table S4 (Figures S3 – S18 ) [ 21 , 34 40 ]. The retention times at 8.91, 13.76, 17.37, and 18.14 min corresponded to the peaks 4, 9, 14, and 15 in the HPLC fingerprint by comparing the peak area, polarity, and spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The content of micranthoside in the male samples was lower than that in the female samples. The content of sakuranin, siebolside B, and isograndidentatin A was higher in the male barks than in the female barks [ 21 ]. The differences in volatile components of mature P. tomentosa flower buds were studied by HS-SPME-GC-MS, which showed that the content of four compounds was different, containing benzyl benzoate, 2-cyclohexen-1-ketone, methyl benzoate, and benzoate.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fingerprints combined with multivariate statistical analysis have been used to classify and discriminate different TCMs sources successfully [34]. In the current study, the spectrum of sample S4 was used as the reference spectrum, and the representative HPLC fingerprints of 21 batches of saffron were established as shown in Figures 2(a e generated representative fingerprints were showed in Figures 2(c) and 2(d).…”
Section: Hplc Fingerprint Analysis and Similarity Analysismentioning
confidence: 99%
“…Large differences exist in biological features between the male and female individuals of dioecious plants, such as physiological, biochemical, and ecological adaptability [12][13][14]. Recently, research have been carried out on the chemical differences and discrimination of male and female individuals of dioecious plants such as barks and flower buds of Populus tomentosa with high-performance liquid chromatography (HPLC), 1 H-nuclear magnetic resonance ( 1 H-NMR), and headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC-MS) in combination with chemometrics [14][15][16]. For M. alba, research on male and female individuals of M. alba focused on sex determination mechanisms and effects of the environment on mulberry saplings' growth [17,18].…”
Section: Introductionmentioning
confidence: 99%